2006
DOI: 10.2176/nmc.46.290
|View full text |Cite
|
Sign up to set email alerts
|

External Carotid Artery Aneurysm Developing After Embolization of a Ruptured Posterior Inferior Cerebellar Artery Aneurysm in a Patient With Cervicocephalic Fibromuscular Dysplasia-Case Report-

Abstract: A 30-year-old man presented with an aneurysm of the left posterior inferior cerebellar artery manifesting as subarachnoid hemorrhage and cerebellar infarction. Angiography demonstrated string-of-beads sign typical of fibromuscular dysplasia (FMD) in the extracranial carotid and vertebral arteries. The aneurysm and the parent artery were successfully embolized with Guglielmi detachable coils. Severe vasospasm developed 1 week after admission, and was treated several times by selective injection of vasodilator. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Castellano et al [18] described a clinical case of severe coronary vasospasm attributable to FMD. The susceptibility of intracranial vasculature to symptomatic vasospasms in FMD patients suffering aneurysmal bleeding has also been reported [16,21,22,23]. Overall, the data regarding possible associations between FMD and post-SAH vasospasm are very limited to date and only based on case reports.…”
Section: Discussionmentioning
confidence: 99%
“…Castellano et al [18] described a clinical case of severe coronary vasospasm attributable to FMD. The susceptibility of intracranial vasculature to symptomatic vasospasms in FMD patients suffering aneurysmal bleeding has also been reported [16,21,22,23]. Overall, the data regarding possible associations between FMD and post-SAH vasospasm are very limited to date and only based on case reports.…”
Section: Discussionmentioning
confidence: 99%
“…Fuse et al [5] shared the case of a 30-year-old male with SAH from a ruptured posterior inferior cerebellar artery aneurysm who underwent vessel sacrifice and multiple transcatheter vasospasm treatments, and who then developed a 3-cm iatrogenic dissecting aneurysm of the external carotid artery. The authors concluded that particular care is needed when performing endovascular interventions in the presence of FMD.…”
Section: Discussionmentioning
confidence: 99%
“…Of relevance to neurosurgeons and neurointerventionalists, the prevalence of cervical dissection and intracranial aneurysms is increased in patients with FMD [2,3,4]. As more such lesions are incidentally discovered, the presence of FMD can serve as discouragement to elective treatment of cerebral aneurysms [5]. There are no reports of outcomes of endovascular interventions through vessels affected by FMD.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the initial angiography findings, the dissection most likely was secondary to the hemodynamic stress on the arterial wall from the hypertensive therapy as the ICA dissection was noticed on the common carotid artery angiogram (Figure 3) without the wire or the catheter entering into the ICA. Hemodynamic stress has been proposed as the potential cause of de novo dissecting aneurysms in FMD patients [11,21]. Stehbens reported the association between hypertension and the development of intracranial aneurysms in this group of patients as well [22].…”
Section: Discussionmentioning
confidence: 99%
“…Arterial dissection can result in focal neurological deficits from either a thromboembolic event or hemodynamic compromise due to exposure of the inner arterial wall layers to the bloodstream or arterial lumen stenosis, respectively [9]. Intracranial aneurysms have 20-50% prevalence in patients with carotid or vertebral involvement suggesting a strong correlation between FMD and brain aneurysms [10][11][12][13]. Additionally, there are reports of FMD patients presenting with aneurysmal subarachnoid hemorrhage (SAH), having a poor prognosis secondary to their susceptibility to cerebral vasospasm (CV) [11,12].…”
Section: Introductionmentioning
confidence: 99%